Types of lexical complexity in English: Syntactic categories and the lexicon - Anderson, John (Adam Mickiewicz University, 2012)
This study focuses on minimal (non-compound, non-phrasal) signs that are nevertheless internally complex in their syntactic categorization. Sometimes this is signalled by morphology – affixation or internal modification. But there are also conversions. In terms of categorial structure, we can distinguish between absorptions, where the source of the base is associated with a distinct category, and incorporation, where the base is categorially constant. Incorporation is thus typically reflected in inflectional morphology. Absorption may be associated with morphological change or conversion – with retention of the base in a different categorization. But categorial complexity may be nonderived, covert: the categorial complexity of an item is evident only in its syntax and semantics.